Child protective services during COVID-19 and doubly marginalized children: International perspectives. (September 2022) - Katz, Carmit; Varela, Natalia; Korbin, Jill E.; Najjar, Afnan Attarsh; Cohen, Noa; Bérubé, Annie; Bishop, Ellen; Collin-Vézina, Delphine; Desmond, Alan; Fallon, Barbara; Fouche, Ansie; Haffejee, Sadiyya; et al.
Abstract: Background: Alongside deficits in children's wellbeing, the COVID-19 pandemic has created an elevated risk for child maltreatment and challenges for child protective services worldwide. Therefore, some children might be doubly marginalized, as prior inequalities become exacerbated and new risk factors arise. Objective: To provide initial insight into international researchers' identification of children who might have been overlooked or excluded from services during the pandemic. Participants and setting: This study was part of an international collaboration involving researchers from Brazil, Canada, Colombia, Israel, South Africa, Uganda, the UK and the USA. Researchers from each country provided a written narrative in response to the three research questions in focus, which integrated the available data from their countries. Method: Three main questions were explored: 1) Who are the children that were doubly marginalized? 2) What possible mechanisms may be at the root? and 3) In what ways were children doubly marginalized? The international scholars provided information regarding the three questions. A thematic analysis was employed using the intersectional theoretical framework to highlight the impact of children's various identities. Results: The analysis yielded three domains: (1) five categories of doubly marginalized children at increased risk of maltreatment, (2) mechanisms of neglect consisting of unplanned, discriminatory and inadequate actions, and (3) children were doubly marginalized through exclusion in policy and practice and the challenges faced by belonging to vulnerable groups. Conclusion: The COVID-19 pandemic can be used as a case study to illustrate the protection of children from maltreatment during worldwide crises. Findings generated the understanding that child protective systems worldwide must adhere to an intersectionality framework to protect all children and promote quality child protection services.